1988
DOI: 10.1097/00004032-198809000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium, Am, Cm and Sr in Ducks Maintained on Radioactive Leaching Ponds in Southeastern Idaho

Abstract: Concentrations of 90Sr, 238Pu, 239,240Pu, 241Am, 242Cm and 244Cm were determined in tissues of mallard ducks (Anas platyrhynchos) maintained for 43-145 d on radioactive leaching ponds in southeastern Idaho. Highest concentrations of transuranics occurred in the gastrointestinal tract, followed closely by feathers. Approximately 75%, 18%, 6% and 1% of the total transuranic activity in tissues analyzed were associated with the bone, feathers, GI tract and liver, respectively. Concentrations in GI tracts were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…12gIin deer thyroids may be a sensitive indicator of contaminants from nuclear fuel processing plants and atmospheric nuclear tests or accidents. Markham et al (1988). Concentrations ol'90Sr, 238Pu, '91240Pu, 241 Am, '2Cm, and "Cm were determined in tissues of mallard ducks (Arias platyrhynochos) maintained for 43 to 145 days on radioactive leaching ponds at the TRA.…”
Section: C-16mentioning
confidence: 99%
See 2 more Smart Citations
“…12gIin deer thyroids may be a sensitive indicator of contaminants from nuclear fuel processing plants and atmospheric nuclear tests or accidents. Markham et al (1988). Concentrations ol'90Sr, 238Pu, '91240Pu, 241 Am, '2Cm, and "Cm were determined in tissues of mallard ducks (Arias platyrhynochos) maintained for 43 to 145 days on radioactive leaching ponds at the TRA.…”
Section: C-16mentioning
confidence: 99%
“…Doses received by individual organisms provide a basis for determining the potential for harm to populations. A number of authors have calculated or estimated doses to ecological receptors from internal and external contamination received at the INEL Fraley et al 1982;Halford 1987;Halford 1987b;Markham et al 1988;Morris et al in preparation). found that some maximally exposed small mammals inhabiting the TRA radioactive waste pond basin received doses that had been found to reduce life expectancy in earlier studies .…”
Section: C-33 Preliminary Qualitative Ecological Risk Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of TCE in samples ber[14][15][16][17][18] 1992, and analyzed by the Lockheed from the Water Reactor Research Test Facility Analytical Laboratory in Las Vegas, Nevada, (WRRTF) distribution system are above the max-according to the same regulations. None of the imum contaminant level of 5 lag/L.…”
mentioning
confidence: 99%